GROUNDWATER POTENTIALS ESTIMATION USING SELF-POTENTIAL METHOD AS AN EARLY PREDICTION OF LAND SUBSIDENCE IN GAMPONG LENGKONG LANGSA CITY - Fajriani, Fajriani; Fadlly, Teuku Andi; Harmawan, Tisna (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
The Self-Potential (SP) method was used to identify changes in the potential groundwater in the area of Gampong Lengkong, Langsa City. The data acquisition technique was carried out with a fixed base technique with a measurement count of four acquisition lines. Research is conducted for two months that July and August are the same to monitor the changes in the SP value associated with the change of SP anomaly. SP value of the acquisition result is used as a reference for estimating the potential of groundwater. Interpretation is made qualitatively and quantitatively. Qualitative interpretation through analysis maps of the isopotential contours compared between the first month and the second month of measurements in the field. The interpretation is quantitatively by assuming the source of the subsurface anomaly fix geometry models of cylinders or spheres is done by the inversion modeling using the Levenberg-Marquardt method. The results showed that there was a reduction in SP value in the second month, indicating the potential shortage of groundwater in the region. The decrease in groundwater potential is also shown in the inversion results, where the result of the calculation of SP anomaly source parameters in the first month is estimated to be at 7.77 meters to 11.05 meters below the ground in the monthly measurements second.Â Â